The Influence of Scramble Learning Models and Motivation Learning on the Results of Citizension Education Class V SD Students State 101766 Bandar Setia - Dewi Lestari; Reh Bungana; Siman Siman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Teachers have a duty to encourage, guide and provide learning facilities to achieve goals. Teachers have a responsibility to see everything that happens in the classroom to help student development. Teachers must be able to carry out their duties properly by first having to understand carefully the matters relating to the teaching and learning process, because the success of the learning process is supported by the ability of the teacher to develop and generate activeness and students in the learning process. The research method used is the Quasi Experiment (Quasi Experimental Method) with the research design as the basis for the implementation of the research is to distinguish the influence of the Inquiry method and the effect of conventional methods on learning outcomes of Citizenship Education in terms of high learning motivation and low learning motivation where the treatment class is class Va student and Vb class. The following is presented sequentially descriptive data regarding: (1) Civics learning outcomes students are taught using scramble learning model, (2) Civics student learning outcomes are taught using the expository model, (3) Civics student learning outcomes have high learning motivation, (4) Civics student learning outcomes have motivation to learn low, (5)Civics learning outcomes of students who have high learning motivation are taught with the Scramble learning model, (6) Civics learning outcomes of students who have low learning motivation are taught with the Scramble learning model, (7) Civics learning outcomes of students who have high learning motivation are taught using the expository learning model, (8) Civics learning outcomes of students who have low learning motivation are taught using the expository learning model.